Identification, antifungal resistance, and genomic characterization of a single Candida auris isolate from urinary tract infection - Li, Jie; Wang, Ziheng; Zheng, Rui; Wang, Yangyan; Guo, Xin; Li, Xiaoning; Zhang, Peng (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo analyze the identification, antifungal resistance, and genomic characteristics of a Candida auris (C. auris) strain isolated from a urine specimen of an ICU patient at Yijishan Hospital, Wannan Medical College, Anhui Province.MethodsThe isolate was identified by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). The susceptibility of the isolates to fungi was determined by measuring the Minimum Inhibitory Concentration (MIC) values using the VITEK 2 COMPACT system. Whole-genome sequencing (WGS) was performed using high-throughput technology. Resistance and virulence genes were annotated using public databases, including NCBI (https://www.ncbi.nlm.nih.gov/, version 2.2.28), DFVF (http://sysbio.unl.edu/DFVF/, version 1.0), PHI-base (http://www.phi-base.org, version 5.0) and KEGG (https://www.kegg.jp/, version 89.1). A phylogenetic tree was constructed through analysis of the 18S rRNA nucleotide sequence.ResultsThe isolate named CAS20503 was identified as C. auris. Antifungal susceptibility testing showed resistance to fluconazole and amphotericin B. Genomic analysis identified resistance genes including ERG11 (azole), FKS1 (echinocandin), ERG3 (polyene), and efflux pumps CDR1, MDR1. Resistance mutations were detected. The virulence genes analyzed based on the DFVF database included CaNik1, CHS2, DUR1,2, HSP90, ICL1, PMT1, PMT2, PMT4, SSD1, TPS2. The host pathogenic genes identified by comparison with the PHI-base database included CaCHS1, ADE2, FAS2, PMR1, CaTPS2, Tfp1. KEGG annotation showed enrichment in infectious disease pathways. The phylogenetic tree constncted based on the nudeotide sequence analysis of 18S rRNA indicated that this strain (Genome accession number: JBPYFS000000000) exhibited a high degree of genomic similarity to the C. auris strain (Genome accession number: CP157510.1), which was isolated in ltaly in 2024 and belonged to clade l (a subset of the South Asian clade).ConclusionThrough an in-depth analysis of strain CAS20503, which was isolated from a urinary tract infection specimen at a tertiary public hospital in Anhui Province (Yijishan Hospital, Wannan Medical College), this study elucidated the drug resistance profiles and genomic characteristics of C. auris. The findings have provided critical evidence for the early identification, diagnosis, and optimization of antifungal therapeutic regimens for infections caused by this pathogen in clinical practice.